(untitled) (Studia Prawnicze / The Legal Studies, 1995)
Fakt podpisania Konkordatu między Stolicą Apostolską i Rzecząpospolitą Polską 28 lipca 1993 r. spowodował szersze zainteresowanie prawem konkordatowym. W toku debaty wokół ratyfikacji konkordatu ujawniły się różne zagadnienia dotyczące nie tyle samej treści przepisów konkordatowych, co szeregu zasad odnośnych do znaczenia regulacji stosunków między państwem a Kościołem w świecie współczesnym w formie dwustronnej umowy międzynarodowej, jaką jest konkordat, i ich aplikacji do konkordatu polskiego. Niniejszy artykuł zawiera ogólną charakterystykę tych zagadnień. The fact of signing the Concordat between the Holy See and the Republic of Poland on 28 July 1993 led to a wider interest in concordat law. In the course of the debate around the ratification of the concordat, various issues emerged concerning not so much the content of the concordat provisions themselves, but a number of principles pertaining to the meaning of the regulation of relations between the state and the Church in the contemporary world in the form of a bilateral international agreement, such as the concordat, and their application to the Polish concordat. This article provides a general overview of these issues.